The Influence of Al-Ti-B on the microstructure of unidirectionally solidified Al-10wt.%Cu-10wt.%Si - Masnur, Dedy; Malau, Viktor; suyitno, Suyitno (Politeknik Negeri Lhokseumawe, 2024)
Many works have reported the role of grain refiners in aluminumsilicon alloy casting in direct chill casting. However, only a few are under the unidirectional solidification condition. Direct chill casting favors equiaxed structures, while unidirectional solidification favors columnar structures. This work investigated the influence of Al-Ti-B on the microstructure of unidirectionally solidified Al-10wt.%Cu-10wt.%Si. The samples were directionally solidified using the Bridgman apparatus. It was cooled at the bottom to a temperature of 650℃, and the temperatures were recorded during the cooling. A representation of the cooling curve was selected, and the solidification parameters were calculated. Metallographic procedures were applied to observe the microstructure across the sample length. The results show that the 0.03wt.%Ti effectively promotes nucleation in many sites. It leads to the formation of equiaxed structures and prevents fine columnar structures from further growth. Due to the magnitude of the cooling rate, the 0.03wt.%Ti exhibits fine columnar, fine equiaxed, coarse equiaxed, and dendrite equiaxed structures at the separated distance from the contact area. This formation is in line with the one produced by the mechanism in direct chill casting. Understanding the grain refiner effect is crucial for optimizing manufacturing processes and achieving desired material properties. The Al-Ti-B addition is not recommended in the propeller manufacturing industry.